Advancements in fiber-reinforced polymer composite materials damage detection methods: Towards achieving energy-efficient SHM systems. (15th October 2021) - Ahmed, Osama; Wang, Xin; Tran, Manh-Vu; Ismadi, Mohd-Zulhilmi
Abstract: The application of fiber-reinforced polymer (FRP) composites is continuously increasing due to their superior mechanical properties and the associated weight advantage. However, they are susceptible to more complex types of damage, and advanced damage characterization systems are required to prevent catastrophic failures. Various non-destructive testing and evaluation (NDT&E) and in-situ structural health monitoring (SHM) techniques have been applied for damage detection in FRP composites. These techniques have been continuously developed to achieve reliable inspections, especially for safety-critical applications such as the aerospace industry. This review presents recent advances in NDT&E techniques and SHM techniques, particularly for damage diagnosis in FRP composites. For selecting the most suitable NDT technique based on specific criteria, the analytical hierarchy process is applied as a decision-making tool to evaluate and rank the NDT techniques. The size of the specimen is found to be the most important criterion that significantly affects technique selection. Finally, the importance of developing in-situ SHM systems is outlined, and different in-situ SHM systems are then reviewed and discussed. This review provides progress of the recent damage characterization techniques and enables researchers to devise selection criteria to select the most appropriate technique for their own work.